Waiting to Exhale: African American Women and Adult Learning Through Movies - Elice E. Rogers (Adult Education Research Conference, 2002)
This paper proposes that movies are a great source for learning especially for African American women. Findings suggest that adult educators will want to look closely at how today’s diverse adults are informed and make meaning via popular culture.